Natural language processing reveals differences in mental time travel at higher levels of self-efficacy - Laurin Plank; Armin Zlomuzica (Scientific Reports)
Abstract The (re-)construction of past and future personal experiences, termed mental time travel (MTT), is highly adaptive and contributes to self-related beliefs and attitudes. Mounting evidence suggests that self-efficacy (SE), the belief that one can overcome obstacles on their own account, is functionally related to MTT. In the present study, we used novel methods for the analysis of MTT narratives based on natural language processing (NLP) to investigate the relation between SE and MTT. We demonstrated that self-efficacious participants remembered and imagined experiences which were semantically less similar and contained a wider variety of contents. Additionally, increased SE was related to a positive reappraisal of personal episodes and reports of a more active role within mental scenarios. In conclusion, NLP appears to be a valuable method to quantify changes to the (re-)construction of personal experience that might support cognitive and emotional functioning.